2015
DOI: 10.1007/s11356-015-5830-7
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of Bacillus thuringiensis var. kurstaki on the hymenopterous parasitic wasp Trichogramma chilonis

Abstract: Most of the detrimental effects of using conventional insecticides to control crop pests are now well identified and are nowadays major arguments for replacing such compounds by the use of biological control agents. In this respect, the bacterium Bacillus thuringiensis var. kurstaki and Trichogramma (Hymenoptera: Trichogrammatidae) parasitic wasp species are both effective against lepidopterous pests and can actually be used concomitantly. In this work, we studied the potential side effects of B. thuringiensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Indeed, studies have highlighted that Cry toxins can delay the development and increase the mortality of trichopteran species whose larvae have an aquatic lifestyle [ 19 , 20 ]. Btk bioinsecticides are also acutely toxic against Trichogramma chilonis females, a tiny egg endoparasitoid hymenopteran used as a biocontrol agent in integrated pest management to control lepidopteran pests on crops [ 21 ] and delay the imago emergence of many Drosophila species [ 22 ]. In vertebrates, Grisolia and colleagues observed that the exposure of Danio rerio fry to different Btk Cry toxins induced lethality and developmental delay [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have highlighted that Cry toxins can delay the development and increase the mortality of trichopteran species whose larvae have an aquatic lifestyle [ 19 , 20 ]. Btk bioinsecticides are also acutely toxic against Trichogramma chilonis females, a tiny egg endoparasitoid hymenopteran used as a biocontrol agent in integrated pest management to control lepidopteran pests on crops [ 21 ] and delay the imago emergence of many Drosophila species [ 22 ]. In vertebrates, Grisolia and colleagues observed that the exposure of Danio rerio fry to different Btk Cry toxins induced lethality and developmental delay [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of studies on the integrated management of H. armigera, the main control method is represented by the use of chemical insecticides, which results in disadvantages because of the high use of toxic substances that are not very selective, showing slow environmental degradation and also potential to bioaccumulation and biomagnification. At the same time, these chemical pesticides can lead to serious consequences such as the target pest resistance, elimination of natural enemies, environmental contamination and risks to human health (Amichot et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Amichot and colleagues have shown that Btk bioinsecticides are acutely toxic against Trichogramma chilonis females, a tiny egg endoparasitoid hymenopteran used as a biocontrol agent in integrated pest management (Amichot et al, 2016). On vertebrates, Grisolia and colleagues observed that the exposure of Danio rerio fry to different Btk Cry toxins induced lethality and developmental delay (Grisolia et al, 2009).…”
Section: Introductionmentioning
confidence: 99%